The Role of Employee Engagement in Mediating the Effects of Quality of Work Life and Self-Efficacy on Employee Performance: (A Study of Employees at the Salatiga City Regional Secretariat) - Pramudya, Dimas Septian Galih; Suhana, Suhana (Universitas KH. Abdul Chalim Mojokerto, 2026)
The employee population at the Salatiga City Regional Secretariat was 111, consisting of 104 ASN (State Civil Apparatus) and 7 P3K (Government Employee with Work Agreement). The sample was drawn using census sampling, resulting in 111 respondents. Primary data were collected using questionnaires, while data analysis was conducted using linear regression. Conclusion: QWL significantly positively impacts employee performance at the Salatiga City Regional Secretariat. Self-efficacy significantly and positively impacts employee performance at the Salatiga City Regional Secretariat. QWL significantly and positively impacts employee engagement at the Salatiga City Regional Secretariat. Self-efficacy has a significant positive effect on employee engagement at the Salatiga City Regional Secretariat. Employee engagement has a significant positive effect on the performance of the Salatiga City Regional Secretariat. Employee engagement mediates the QWL effect on the performance of the Salatiga City Regional Secretariat. Employee engagement mediates self-efficacy effect on the performance of the Salatiga City Regional Secretariat.